DOES SLEEP QUALITY SERVE AS A MEDIATOR BETWEEN WELL-BEING AND ACADEMIC ACHIEVEMENT? - Yulia Ayriza; Farida Agus Setiawati; Siti Rohmah Nurhayati; Sasanty Ratna Gumelar; Eka Putri Desy Rahmawati Sholeha (Jurnal Cakrawala Pendidikan, 2019)
The transition from high school to college "forces" freshmen students to lead a brand new life until they eventually manage to adapt to the new environment and all its activities. Freshmen students who failed to adapt themselves to the environment will face various problems including the degradation of well-being which consequently affects their academic achievement and gets worse when it affects their sleep quality. This expost facto research design aims to examine whether sleep quality serves as a mediator between well-being and academic achievement. The participants comprise 231 freshmen students of a public university in Yogyakarta, Indonesia for the academic year 2017. They were collected using multilevel randomization conducted on seven existing University faculties. The data were collected using Positive Affect and Negative Affect Schedule (PANAS), Life Satisfaction, and Pittsburg Sleep Quality Index (PSQI) and were analyzed using multiple regression technique. The results of the analysis demonstrated that sleep quality does not significantly mediate the relationship between well-being and academic achievement of freshmen students. However, this research found that the negative affect which constitutes a component of well-being significantly results in poor sleep quality. Therefore, it is highly recommended to improve well-being through prevention on the development of negative affect on students.